Modern Understanding of the Pathogenesis of Type 3C Diabetes (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Type 3c diabetes mellitus (T3cDM), also known as pancreatogenic diabetes, arises due to exocrine pancreatic disorders such as chronic pancreatitis, pancreatic necrosis, or surgery. Recent research highlights the multifactorial nature of T3cDM, involving not only β-cell destruction but also inflammation-driven islet remodeling, immune dysregulation, oxidative and ER stress, fibrosis, and hormonal imbalances. Key molecular mechanisms include activation of inflammasomes (NLRP3), JAK/STAT, and NF-κB pathways, suppression of Nrf2-mediated antioxidant defense, and cytokine-induced β-cell apoptosis. In addition, disturbances in incretin signaling, α- and δ-cell function, and exocrine insufficiency exacerbate metabolic instability. This review synthesizes current data on the morphofunctional alterations and immunometabolic mechanisms underlying T3cDM, underscoring the need for early detection, integrated treatment strategies, and preservation of residual islet function.